Efficacy and Safety of Infliximab Therapy and Predictors of Response in Korean Patients with Crohn's Disease: A Nationwide, Multicenter Study - Choi, Chang Hwan; Song, In Do; Kim, Young-Ho; Koo, Ja Seol; Kim, You Sun; Kim, Joo Sung; Kim, Nayoung; Kim, Eun Soo; Kim, Jae Hak; Kim, Ji Won; Kim, Tae Oh; Kim, Hyun Soo; et al. (Yonsei medical journal, 2016)
Infliximab is currently used for the treatment of active Crohn's disease (CD). We aimed to assess the efficacy and safety of infliximab therapy and to determine the predictors of response in Korean patients with CD. A total of 317 patients who received at least one infliximab infusion for active luminal CD (n=198) and fistulizing CD (n=86) or both (n=33) were reviewed retrospectively in 29 Korean referral centers. Clinical outcomes of induction and maintenance therapy with infliximab, predictors of response, and adverse events were evaluated. In patients with luminal CD, the rates of clinical response and remission at week 14 were 89.2% and 60.0%, respectively. Male gender and isolated colonic disease were associated with higher remission rates at week 14. In week-14 responders, the probabilities of sustained response and remission were 96.2% and 93.3% at week 30 and 88.0% and 77.0% at week 54, respectively. In patients with fistulizing CD, clinical response and remission were observed in 85.0% and 56.2% of patients, respectively, at week 14. In week-14 responders, the probabilities of sustained response and remission were 94.0% and 97.1%, respectively, at both week 30 and week 54. Thirty-nine patients (12.3%) experienced adverse events related to infliximab. Serious adverse events developed in 19 (6.0%) patients including seven cases of active pulmonary tuberculosis. Infliximab induction and maintenance therapy are effective and well tolerable in Korean patients with luminal and fistulizing CD. However, clinicians must be aware of the risk of rare yet critical adverse events.